The structural architecture of the reactivated Rennick Geodynamic Belt (Northern Victoria Land, East Antarctica) - Cianfarra P.; Federico L.; Crispini L.; Capponi G.; Salvini F. (2018)
The Rennick Geodynamic Belt (RGB) is a regionally-sized deformation corridor separating the tectonic units of the Northern Victoria Land (NVL) and of the East Antarctic craton (EAC). It develops along the onland propagation of the Tasman Fracture Zone of the Southern Ocean between Australia and East Antarctica. The RGB is characterized by a length exceeding 100 km and consists of regional fault strands, including the Rennick Fault. Previous studies revealed that this deformation corridor was characterized by poly-phased tectonic movements since Cambro-Ordovician times (Capponi et al., 1999; Federico et al. 2010). The brittle deformation architecture associated to these fault zones, the sharp-asymmetric subglacial morphology, and the geophysical signature at the Rennick Glacier, as well as the geodetic investigations in NVL, strongly suggest that the region is involved in Cenozoic tectonic activity. In this work we present the results of a multi-scalar study aimed to highlight the Meso-Cenozoic tectonic evolution/reactivation of the RGB. The analysis is based on a twofold approach that includes inversion of fault-slip data and lineament domain analysis. The identification of the paleostress field(s) responsible for brittle deformation associated to the main Rennick Faults and the adjacent fault strands is based on the fault and fracture inversion performed through an original methodology based on the multiple Montecarlo approach. Results from the different inversion approaches are also discussed. The lineament detection from synthetic scaled images (MODIS mosaic of Antarctica) of the landscape (including both the ice sheet surface and the outcropping mountains) is performed with automatic procedures (Cianfarra and Salvini, 2014; Cianfarra and Salvini, 2015; Lucianetti et al, 2017). Domain identification follows a two-step processing: i. after the polynomial Gaussian fit by grid analysis, the association of the found Gaussian peaks of adjacent analyses allows to identify the Gaussian domains; ii. lineaments are ...